Practical orientation of mathematical disciplines in secondary schools of Ukraine at the beginning of the 20th century (Pedagogy of Higher and Secondary Education, 2012)
Vykhrushch N. Practical orientation of mathematical disciplines in secondary schools of Ukraine at the beginning of the 20th century.The article generalizes positive historical experience of teaching mathematical disciplines in secondary schools of Ukraine at the beginning of the 20th century. The peculiarities of content and methods of teaching mathematical disciplines in secondary schools of Ukraine in the mentioned period have been defined.
Keywords: arithmetic; algebra; geometry; methods